Dispersion of 137Cs concentration in the basins of the Aegean Sea - Pappa, F. K.; Patiris, D. L.; Eleftheriou, G.; Tsabaris, C.; Kokkoris, M.; Vlastou, R.; Kaberi, H. (HNPS Advances in Nuclear Physics, 2020)
The anthropogenic radionuclide 137Cs is used as a valuable oceanographic tracer for the study of sea water masses identification and water movement. In the present work, 137Cs activity concentrations have been investigated in deep basins of Aegean Sea. Seawater samples were collected from five different sampling stations, during scientific oceanic campaigns from the period March to April 2008. The applied methodology was based on the adsorption of radiocaesium from dissolved AMP (Ammonium Phosphomolybdate Hydrate) in 20 L water samples. Moreover, during the pre- concentration procedure, the 134Cs was used as reference tracer for determining the chemical efficiency and consequently to measure the activity concentration in a High Purity Ge detector. In terms of vertical records, the activity concentration in the selected basins ranged between 3-8.5 Bq/m3, depending on the region and the depth of the basins. The higher concentration (8.5 Bq/m3) was found in the region between Lemnos Island and the narrows of Dardanelles. The maximum concentrations were observed at the North Aegean Sea basins, between 20 and 40 m of depth, caused by the water masses coming from the Black Sea. At the Cretan Sea the vertical activity concentration of 137Cs was homogeneous down to 2000 m depth, with an exception at the 800 m where it was decreasing significantly due to the transient deep-water masses from Adriatic Sea.